Apresentação - Fernandes, Felipe Bruno Martins; Nascimento, Mariângela Moreira; Silva, Shirlei Santos de Jesus; Santos, Jeferson Reis (Cadernos de Gênero e Diversidade, 2015)
Elementos Pré-Textuais do Número.